ENVIRONMENTAL IMPLICATIONS OF CELL PHONES PENETRATION AND DISPOSAL IN KENYA (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Kenya has over six million active  mobile subscribers who may at some point want to replace or   get rid of old mobile phones. A big number of the mobile phones were recently switched off for not being genuine without a prober mechanism being put in place for the disposal. If every affected individual or otherwise disposed off phones by throwing it away then there could a serious ecological disaster in waiting. Cell phones are hazardous materials because of electromagnetic radiation and electronic composition. They have substances such as antimony, arsenic, beryllium, cadmium, copper, lead, nickel and zinc which belong to a class of chemicals known as persistent toxins. These toxins pollute and remain in the environment for long periods. There are ill-effects of wireless and telecommunication devices on the environment are disastrous.  The increased use of high resolution LCD screens leads to a potentially devastating environmental challenge. There is no clear policy frame work on e-waste management with a special focus on used mobile phones in the country.  A proper disposal mechanism of wireless and telecommunication devices is a necessity in Kenya.